Distinguished African American scientists of the 20th century - Kessler, James H. (Oryx Press, 1996)
From George Washington Carver to Dr. Mae Jemison, African Americans have been making outstanding contributions in the field of science. This unique resource goes beyond the headlines in chronicling not just the scientific achievements but also the lives of 100 remarkable men and women. Each biography provides an absorbing account of the scientist's struggles, which often included overcoming prejudice, as they pursued their educational and professional goals.